UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KECOMBRANG Etlingera elatior (Jack) R.M.Sm TERHADAP Salmonella typhi - Eko Kusumawati; Risa Supriningrum; Reza Rozadi (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Research Test Antibacterial Activity of Ethanol Extracts of Leaves kecombrang against Salmonella typhi aims to determine the antibacterial activity of ethanol extract of leaves kecombrang against Salmonella typhi. The extract used is kecombrang leaf extract prepared by maceration using ethanol 95%, extracts obtained test chemical classes of compounds to determine the content of the active compound. Antibacterial activity test conducted at five concentrations of the extract is 20%, 40%, 60%, 80%, and 100%. Inhibition zone measurement results are then analyzed using One Way ANOVA with SPSS 20 to determine whether there is a difference at each concentration. The results showed kecombrang leaf ethanol extract 20%, 40%, 60%, 80%, and 100% produce inhibition zone diameter 3.9 mm; 6.5 mm; 6.75 mm; 7:45 mm; and 9:28 mm, 0 mm for the negative control and positive control 32.61 mm. The test results show the class of secondary metabolites kecombrang leaf ethanol extract contains tannin, saponin, and flavonoids. Of statistical tests concluded there were significant differences of treatment results in inhibition of the respective concentrations of ethanol extracts of leaves kecombrang